Morocco : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses two selected issues related to the economy of Morocco: fiscal multipliers and efficiency of public spending on education in Morocco. Because of the several exogenous shocks to the economic condition of Morocco, interest in estimating the size of the fiscal multiplier has increased in recent past. To better understand the size of the fiscal multiplier, it may be necessary to better comprehend the relationship between key macroeconomic variables in both the short and long run. Despite spending substantially on education in compared to other countries, youth unemployment in Morocco is high. This paper aims to help tackle youth unemployment by focusing on the efficiency of public spending on education.